Investigation of High-Intensity Interval Training (HIIT) Studies in Tennis and Badminton Players - Yıldız Yaprak; Fikret Ozturk (ümit doğan üstün, 2021)
The aim of this review was to examine the studies on high-intensity interval training (HIIT) applied in tennis and badminton. Considering the duration of the tennis and badminton match, these sports are seen as an aerobic sports. However, the short and high intensity rallies in the tennis match also show that it is an anaerobic sport, at the same. There are very high intensity and intermittent rallies lasting 8-10 seconds in prolonged competitions. In other words, both sports require both aerobic and anaerobic endurance during the competition. This endurance is very important not only for the match, but also for the training session as endurance is required for training to be carried out efficiently. Therefore, coaches want to develop aerobic endurance first during the general preparation period at the beginning of the season. In the classical endurance training method, the training session is planned at least 45-50 minutes and 3 times per week. During this period, technical and tactical training are secondary, so there is no time problem to improve endurance. However, as the season progresses, it will be difficult to find the necessary time to maintain aerobic and anaerobic endurance when technical-tactical training becoms important in the special preparation and competition period. Studies show that, HIIT eliminates this time problem, and although it is a very short training method, it is effective in improving aerobic and anaerobic endurance.